Gagasan Penerapan Hukum Progresif Terhadap Pelaku Kejahatan Kerah Putih - Supriyono B.S (Universitas Budi Luhur, 2017)
The positive law or legal positivism which among others imposed in Indonesia, separates expressly between law and morals or between applicable law and the supposed law (das sein and das sollen). In the positivist attitude, there is no other law except the command of the lawgivers. Even part of the flow of positive law is known as legism, which argues that law is identical with the law. The term white collar crime was coined by Edwin Sutherland in 1993 described as a crime committed by business-related individuals or a top-class socioe-conomic. This paper is intended to examine the positive law enforcement and try to offer legal action against white collar crime in Indonesia, especially by the Corruption Eradication Commission (KPK) which is increasingly facing serious obstacles from unexpected or suspected white-collar criminals, especially which has political power. This study is a document study as one form of qualitative research that gives greater space to subjective considerations of researchers when compared with quantitative research. Therefore this paper is limited to offering ideas, not a comprehensive study that considers relevant aspects. The data used are secondary, both from books and mass media coverage.